A novel GATA transcription factor GATAβ4 promotes vitellogenin transcription and egg formation in the silkworm Bombyx mori. (April 2019) - Liu, Hongling; Lin, Ying; Shen, Guanwang; Gu, Jianjian; Ruan, Yang; Wu, Jinxin; Zhang, Yujing; Li, Kairong; Long, Wei; Jia, Linbang; Xia, Qingyou
Abstract: GATA transcription factors (GATAs) are widely expressed among various organisms and belong to the zinc finger protein family. GATA transcription factors play important roles in the proliferation, differentiation, and development of eukaryotes. Previous studies have shown that GATA participates in oogenesis by selective splicing in silkworms. In this study, we investigated the function of GATAs during vitellogenesis using female silkworms ( Bombyx mori ). Six types of GATA transcription factors were successfully cloned in the fat body of silkworms during the wandering stage and only BmGATAβ4 induced the activity of the Bombyx mori vitellogenin ( BmVg ) promoter. Furthermore, BmVg and BmGATAβ4 exhibited similar expression patterns in the fat body of female silkworms during the wandering stage. Electrophoretic mobility shift assays, cell transfection assays, and chromatin immunoprecipitation showed that BmGATAβ4 was involved in regulating the transcription of BmVg by directly binding to the GATA cis -response element 1 (CRE1) and GATA cis -response element 2 (CRE2) in the promoter of the BmVg gene. RNA interference of BmGATAβ4 in female silkworms downregulated BmVg transcription, resulting in a decrease in egg size and shortening of the length of egg tubes relative to the control. In summary, our results indicated that BmGATAβ4 bound to the GATA CRE1 and CRE2 motifs in the BmVg promoter to upregulate BmVg expression in the fat body of female silkworms. Graphical abstract: Image 1 Highlights: BmGATAβ4 induces the activity of the vitellogenin ( BmVg ) promoter. BmGATAβ4 regulates BmVg transcription by directly binding to GATA CRE1 and CRE2 DNA elements. BmVg and BmGATAβ4 exhibit similar expression profiles in the fat body of female silkworms. BmGATAβ4 knockdown affects reproduction in female silkworms.